2022
DOI: 10.1039/d2nr01172g
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven sequential shape transformation of block copolymer particles through three-dimensional confined self-assembly

Abstract: Shape-controlled block copolymer (BCP) particles that respond to light stimulus have drawn great attentions due to their promising applications in smart materials, yet the polymeric particles with light-triggered controllable sequential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A series of polymer particles composed of PS- b -P2VP BCPs and each additive were prepared by using solvent-evaporative emulsions with a molar ratio of additive to 2VP unit ( x ) ranging from 0 to 2.0. In all cases, both PS and P2VP domains have neutral surroundings by using a mixture of CTAB and PVA surfactants, where each surfactant preferentially interacts with PS and P2VP, respectively. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of polymer particles composed of PS- b -P2VP BCPs and each additive were prepared by using solvent-evaporative emulsions with a molar ratio of additive to 2VP unit ( x ) ranging from 0 to 2.0. In all cases, both PS and P2VP domains have neutral surroundings by using a mixture of CTAB and PVA surfactants, where each surfactant preferentially interacts with PS and P2VP, respectively. , …”
Section: Resultsmentioning
confidence: 99%
“…This structure is described by interconnected stacked PS discs with a distance of 220 nm, where the remarkably increased spacing is attributed to the repulsion of the adjacent swollen quaternized P2VP layers (Figure S4). ,, Therefore, the ellipsoid with swelled discs is distinguished by the extensive swelling of P2VP layers interconnected between the disc-like PS domains, compared to conventional ellipsoids. Consequently, the average AR values of the particles significantly increased from 3.6 ( x = 0.5) for ellipsoids to 7.8 ( x = 0.6), 8.9 ( x = 0.8), and 10.9 ( x = 1.0) for ellipsoids with swelled discs.…”
Section: Resultsmentioning
confidence: 99%
“…ideal noninvasive stimulus, which can offer the high level of temporal‐spatial resolution to tune the self‐assembled structure of BCPs confined in the emulsion droplet. [ 6,11,74,85‐86 ] In our previous work, we synthesized a series of azo‐containing trimethylammonium bromide surfactants (AzoC x , while x is the length of hydrophobic alkyl chain.) and applied them to the confined self‐assembly of PS‐ b ‐P4VP block copolymers within emulsion droplet.…”
Section: Tuning the Self‐assembled Morphologies Of Bcp Particles Unde...mentioning
confidence: 99%
“…Therefore, it is an interesting method to tune the shape and morphology of as‐prepared BCP particles by external stimuli if we introduce the stimuli‐responsive polymers or additives into the confined self‐assembly of BCPs initially. [ 6,7,11,73‐78 ] It has been reported that the solubilities of P2VP and P4VP in water are highly related to pH value. Klinger et al .…”
Section: Tuning the Self‐assembled Morphologies Of Bcp Particles Unde...mentioning
confidence: 99%
“…Over the last decade, various strategies have been proposed to realize the neat organization of NPs into high-level superstructures, such as the polymer template assembly, , solvent evaporation, , hydrophobic aggregation , and interfacial assembly. , For example, Zhu et al reported a “rapid liquid–liquid interface assembly” strategy to generate a non-close-packed gold nanoparticle (AuNP) superlattice monolayer with a tunable interparticle distance, which was further utilized as a nonfloating gate memory device . Nevertheless, in most hierarchical assembly processes, the final shape and consistency of the superstructures are still largely dependent on the free energy of the system. Moreover, the general problem in the construction of the functional NP superlattice is that it is extremely difficult to achieve flexible regulation of the specific shape and structure in the hierarchical assembly process using the same NP building blocks, thus greatly increasing the complexity of synthesizing different colloidal NPs. Very recently, Nie et al modified the NPs with complementary reactive polymers.…”
Section: Introductionmentioning
confidence: 99%